2005
DOI: 10.1007/s10722-004-5541-2
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Genetic Diversity in the Brassica napus L. Gene Pool Using SSR Markers

Abstract: Genetic diversity throughout the rapeseed (Brassica napus ssp. napus) primary gene pool was examined by obtaining detailed molecular genetic information at simple sequence repeat (SSR) loci for a broad range of winter and spring oilseed, fodder and leaf rape gene bank accessions. The plant material investigated was selected from a preliminary B. napus core collection developed from European gene bank material, and was intended to cover as broadly as possible the diversity present in the species, excluding swed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
122
1
7

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(148 citation statements)
references
References 16 publications
14
122
1
7
Order By: Relevance
“…Molecular analyses confirmed that these three groups represent distinct gene pools (Song et al, 1988;Diers and Osborn, 1994). Our selection of oilseed accessions included both winter and spring types, which were shown to be differentiated gene pools (Diers and Osborn, 1994;Lombard et al, 2000;Hasan et al, 2006) and accessions from broad geographic origins, which was shown to correlate with the patterns of genetic diversity in this germplasm (Diers and Osborn, 1994;Chen et al, 2008). Most of the cultivars (22 out of 29) were represented by a single genetically homogeneous line, which was obtained after several generations of selfing (Table 1).…”
Section: Plant Materialssupporting
confidence: 54%
See 1 more Smart Citation
“…Molecular analyses confirmed that these three groups represent distinct gene pools (Song et al, 1988;Diers and Osborn, 1994). Our selection of oilseed accessions included both winter and spring types, which were shown to be differentiated gene pools (Diers and Osborn, 1994;Lombard et al, 2000;Hasan et al, 2006) and accessions from broad geographic origins, which was shown to correlate with the patterns of genetic diversity in this germplasm (Diers and Osborn, 1994;Chen et al, 2008). Most of the cultivars (22 out of 29) were represented by a single genetically homogeneous line, which was obtained after several generations of selfing (Table 1).…”
Section: Plant Materialssupporting
confidence: 54%
“…Our worldwide sample encompassed three main B. napus gene pools (ssp oleifera, ssp rapifera, and ssp pabularia), included both winter and spring oilseed types (Diers and Osborn, 1994;Lombard et al, 2000;Hasan et al, 2006), and thus represented a major part of B. napus genetic diversity. Although phenotyping other B. napus accessions could provide supplementary information, the dichotomy of meiotic behaviors found here certainly highlights the overall variation present in this species, which contains germplasm of shared recent common ancestry (Prakash and Hinata, 1980;Allender and King, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The short domestication history of this species and the concentrated breeding efforts made during the 1970s to improve the quality of its oil led to a reduction in the genetic diversity of modern rapeseed (Hasan et al 2005). In addition, rapeseed exhibits strong eco-geographical differentiation into spring and winter forms, with the former being commonly grown in northern latitudes and in Australia, whereas the latter are primarily cultivated in Western Europe (Bus et al 2011).…”
Section: Nuementioning
confidence: 99%
“…Oilseed rape (Brassica napus L.) is the most important source of vegetable oil and the second most important oilseed crop in the international oilseed market after soybean (Hasan et al, 2006). Brassica napus is an amphidiploid (AACC genome,2n = 38) and is believed to have arisen by inter-specific hybridization between diploid Brassica rapa L. (AA genome,2n = 20) and Brassica oleracea L. (CC genome,2n = 18).…”
Section: Introductionmentioning
confidence: 99%